Pengawasan Oleh Kepala Desa Dalam Upaya Meningkatkan Disiplin Kerja Perangkat Di Desa Mekarsari Kecamatan Pagelaran Kabupaten Cianjur - Yuliawati, Neli; Sartika, Farida; Hermawan, Nanang Juhandi (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the role of the Village Head in supervising village officials to improve work discipline in Mekarsari Village, Pagelaran District, Cianjur Regency. The background of this research is the low level of work discipline among village officials due to weak internal supervision systems, reflected in violations of working hours, task delays, and lack of adherence to work procedures. The study employs a descriptive analytical method with a qualitative approach, collecting data through literature review, observation, interviews, and questionnaires distributed to 56 respondents. The results indicate that the supervision carried out by the Village Head-including setting work standards, regulating working hours, assigning tasks based on job descriptions, evaluating, inspecting work results, measuring performance, and providing feedback-has been effective and significantly contributes to improving the work discipline of village officials. Supervision that is participatory, transparent, and accountable serves not only as a control tool but also as a coaching instrument that fosters sustainable discipline awareness. Therefore, the Village Head’s supervision is key to creating a professional village administration and enhancing the quality of public services at the village level.